2008
DOI: 10.1073/pnas.0802531105
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of opiate-induced apoptosis by human recombinant growth hormone in murine foetus primary hippocampal neuronal cell cultures

Abstract: Previous studies have shown that chronic opiates may inhibit cell growth and trigger apoptosis leading to impaired cognitive capabilities in both humans and other mammals. In contrast, growth hormone (GH) has been demonstrated to stimulate cell growth and counteract apoptosis. GH has also been shown to improve learning and memory in both human and rodents. In this work, we demonstrate that GH may reverse opiate-induced apoptosis in cells derived from prenatal mouse hippocampus. Primary hippocampal cell culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 44 publications
2
54
1
Order By: Relevance
“…Interestingly, there is sometimes an association between substances promoting regeneration by enhancing cell proliferation and cell survival. Although GH treatment has not previously been shown to enhance cell proliferation in the adult brain, it has been shown in primary cultures of murine fetal hippocampus to enhance cell survival via suppressing the apoptotic marker caspase-3 (Svensson et al 2008).…”
Section: Significance Of New Cells In the Adult Brainmentioning
confidence: 95%
“…Interestingly, there is sometimes an association between substances promoting regeneration by enhancing cell proliferation and cell survival. Although GH treatment has not previously been shown to enhance cell proliferation in the adult brain, it has been shown in primary cultures of murine fetal hippocampus to enhance cell survival via suppressing the apoptotic marker caspase-3 (Svensson et al 2008).…”
Section: Significance Of New Cells In the Adult Brainmentioning
confidence: 95%
“…In addition, a recent study showed that chronic morphine significantly and dosedependently attenuates neuronal cell density in cultured hippocampal cells from murine fetus (Svensson et al, 2008). The ability of morphine as well as other opioids to inhibit cell growth and induce apoptosis is already known from previous work as described earlier in this section (see section 4).…”
Section: Reversal Of Opioid-induced Impairments By Growth Hormonementioning
confidence: 77%
“…The ability of morphine as well as other opioids to inhibit cell growth and induce apoptosis is already known from previous work as described earlier in this section (see section 4). Therefore, the decline observed in neurite outgrowth in the mouse hippocampal primary cell cultures (Nyberg, 2009;Svensson et al, 2008) was expected, and a consequence of this decline should be that markers of apoptosis, such as lactate dehydrogenase (LDH) and caspase-3, will be affected. In fact, the activity and level of these enzymes were found to be significantly enhanced (Svensson et al, 2008).…”
Section: Reversal Of Opioid-induced Impairments By Growth Hormonementioning
confidence: 99%
See 2 more Smart Citations